UTILIZING ARTIFICIAL INTELLIGENCE TO PREDICT CONSUMER ACTIONS AND MARKET TRENDS IN E-COMMERCE - Xalilova Oyshaxon Sadriddin qizi (Modern American Journals, 2025)
This paper explores the cultural differences in politeness strategies between Uzbek and English communication. Drawing on Brown and Levinson's politeness theory and Hofstede's cultural dimensions, the study highlights how linguistic choices reflect broader societal values such as collectivism and individualism. Through comparative analysis, it examines greetings, requests, apologies, and non-verbal behavior, illustrating how cultural norms shape expressions of respect and social harmony. Understanding these differences is vital for effective cross-cultural communication and reducing misunderstandings in global interactions.
Keywords: Uzbek communication, English politeness, cultural differences, politeness strategies, cross-cultural pragmatics.